Linea Alba Surgical Hernia.: analysis and lndication of Repair Procedures. - Croci, Fabio; Pérez Penco, Ernesto; Cordal, Adriana; Pereira, Jorge (Cirugía del Uruguay, 1984)
Linea alba surgical hernia are not only the most frequent of all abdominal parietal pathology, but they are also aggravated by a high overall rata of recurrencies in their repairing. Consequently, a careful revisíon of the different repairing procedures must be carried out. The object of this work · is a systemátic study of methods currently in. use and indications in this respect.